Pengaruh Rasio Leverage terhadap Harga Saham pada Industri Telekomunikasi di Bursa Efek Indonesia Periode 2014-2017 - Syahril Syahril (Universitas Batanghari Jambi, 2019)
This study aims to analyze whether ratio leverage have a significant or partial effect on stock prices in industry telecomunication in the Indonesian stock exchange for the period 2014-2017. This researc is a descriptive analysis method using qualitative and qualtative descriptive analysis. The analytical tool of this research is the same as the analytical method, namely multiple linear regression using log. The results of the study indicate that simultaneously from this study shows the effect of ratio leverage on stock prices in the industry telecomunication in the Indonesia Stock Exchange for the period 2014-2017. Simultaneously with the number of Fcount 5,287 and Ftable 3.49, it can be seen thatFcount> Ftable is 5,287> 3.49, meaning that there is a significant effect on debt to equtyratio,long term debt to equtyratio,time interest earned ratioon stock prices. Partial influence on the effect of debt to equity ratio,long term debt to equity ratio,time interest earned ratio on stock prices in the industry telecomunication on the IndonesiaStock Exchangefor the period 2014-2017 with the number of Debt to equity ratio tcount-1,795 and ttable2,17881 is the meaning tcount < ttable , -1,795<2,17881, meaning that the Debt to equity ratio does not have a positive effect on against the stock price, Long tem debt to equity ratio tcount2,454 and ttable 2,17881 is the meaning tcount > ttable , 2,454>2,17881, meaning that the Long term debt to equity ratio does have a positive effect on against the stock price and Time interest earned ratio tcount0,814 and ttable 2,17881 is the meaning tcount < ttable , 0,814< 2,17881 meaning that the Time interest earned ratio does not have a positive effect on against the stock price period 2014-2017.